Nanoscale stabilization of the scheelite-type structure in La0.99Ca0.01NbO4 thin films. Issue 6 (14th February 2015) - Tealdi, Cristina; Quartarone, Eliana; Mustarelli, Piercarlo; Malavasi, Lorenzo
<x xml:space="preserve">Abstract</x> Room temperature stabilization of the tetragonal scheelite-type structure is achieved in nanostructured La0.99Ca0.01NbO4 thin films.